Public Financial Management in the Health Sector : An Assessment at the Local Government Level in Malawi - Piatti-Funfkirchen, Moritz; Chansa, Collins; Nkhoma, Dominic (World Bank, Washington, DC, 2021)
This study assesses the extent to which public financial management (PFM) in Malawi supports health service provision at the local government level. Using a conceptual framework that links the budget cycle to health service provider management and service delivery goals, the study assesses how the various stages of the budget cycle affect service delivery at health centers and hospitals. Government and faith-based health providers, known as Christian Health Association Malawi (CHAM), are assessed separately. The study provides insights into provider autonomy and flexibility; financial management capacity; payment arrangements; and the performance orientation of budget provisions or purchasing. The results suggest that significant gaps exist, which undermine the service delivery goals of efficiency, quality, equity, and accountability of service provision. A summary of the findings is presented in the report. It provides complimentary guidance as to how PFM systems facilitate provider management and service delivery at district level health centers and hospitals. Findings and recommendations from the study are expected to support decision makers and practitioners with ongoing PFM reforms.